Sex Hormones Regulate Cytoskeletal Proteins Involved in Brain Plasticity - Hansberg-Pastor, Valeria; González-Arenas, Aliesha; Piña-Medina, Ana Gabriela; Camacho-Arroyo, Ignacio (Frontiers in Psychiatry, 2015)
In the brain of female mammals, including humans, a number of physiological and behavioral changes occur as a result of sex hormone exposure. Estradiol and progesterone regulate several brain functions including learning and memory. Sex hormones contribute to shape the central nervous system by modulating the formation and turnover of the interconnections between neurons as well as controlling the function of glial cells. The dynamics of neuron and glial cells morphology depend on the cytoskeleton and its associated proteins. Cytoskeletal proteins are necessary to form neuronal dendrites and dendritic spines, as well as to regulate diverse functions in astrocytes. The expression pattern of proteins such as Actin, Microtubule Associated Protein 2, Tau and Glial Fibrillary Acidic Protein changes in a tissue-specific manner in the brain, particularly when variations in sex hormone levels occur during the estrous or menstrual cycles or pregnancy. Here we review the changes in structure and organization of neurons and glial cells that require the participation of cytoskeletal proteins whose expression and activity are regulated by estradiol and progesterone.